Significant Independent Predictors of Vitamin D Deficiency in Inpatients and Outpatients of a Nephrology Unit. (12th May 2013) - Bentli, Recep; Taskapan, Hulya; Toktaş, Halil; Ulutas, Ozkan; Ozkahraman, Adnan; Comert, Melda
Abstract : Aims . Kidney disease was found to be a major risk factor for vitamin D deficiency in a population study of patients hospitalized. The aims of the study were to describe the prevalence of vitamin D deficiency inpatients and outpatients in a nephrology department during fall and to evaluate effect of assessing serum 25-hydroxyvitamin D (25(OH)D) levels and previous supplementation of cholecalciferol on vitamin D status. Methods . We studied 280 subjects in total, between October and January. The subjects were recruited from the following two groups: (a) inpatients and (b) outpatients in nephrology unit. We examined previous documentary evidence of vitamin D supplementation of the patients. Results . The prevalence of vitamin D deficiency among these 280 patients was 62, 1% (174 patients). Fifty-three patients (18.9%) had severe vitamin D deficiency, 121 patients (43.2%) moderate vitamin D deficiency, and 66 patients (23.6%) vitamin D insufficiency. In logistic regression analysis female gender, not having vitamin D supplementation history, low serum albumin, and low blood urea nitrogen levels were significant independent predictors of vitamin D deficiency while no association of vitamin D deficiency with diabetes mellitus, serum creatinine, eGFR, and being hospitalized was found. Conclusion . Vitamin D deficiency, seems to be an important problem in both inpatients and outpatients of nephrology. Monitoring serum 25(OH)D concentrations regularly and replacement of vitamin D are important. Women in Turkey are at more risk of deficiency and may therefore need to consume higher doses of vitamin D.